Central Nervous System-type Neuroepithelial Tumors and Tumor-like Proliferations Developing in the Gynecologic Tract and Pelvis: Clinicopathologic Analysis of 23 Cases. (November 2018) - Murdock, Tricia; Orr, Brent; Allen, Sariah; Ibrahim, Junaid; Sharma, Rajni; Ronnett, Brigitte M.; Rodriguez, Fausto J.
Abstract : Central nervous system (CNS)-type tumors and tumor-like proliferations arising in the gynecologic tract and pelvis are rare. Clinicopathologic features of 23 cases are reported using the current WHO classification system for CNS tumors, with selected relevant immunohistochemical and molecular genetic analyses when possible. There were 12 embryonal tumors, including 7 medulloepitheliomas, 2 embryonal tumors (not otherwise specified), 1 embryonal tumor with multilayered rosettes, 1 embryonal tumor with features of nodular desmoplastic medulloblastoma, and 1 medulloblastoma with extensive nodularity, with primary sites including ovary (7), uterus/endometrium (3), and pelvis (2). Six ovarian tumors had associated germ cell tumors (3 immature teratomas [1 also with yolk sac tumor], 2 mature cystic teratomas, and 1 yolk sac tumor). These tumors typically had some expression of synaptophysin (10/10), GFAP (5/9), S100 (3/6), and NeuN (3/3) and were negative for C19MC amplicon by fluorescence in situ hybridization (0/5). There were 6 glial tumors, including 3 ependymomas (1 anaplastic), 1 oligodendroglioma, not otherwise specified, 1 pilocytic astrocytoma, and 1 atypical glial proliferation after therapy of a high-grade high-stage immature teratoma, with primary sites including ovary (4), fallopian tube (1), and pelvic sidewall (1). Four ovarian tumors had associated teratomas (2 immature and 2 mature). These tumors expressed GFAP (5/6), OLIG2 (2/3), and S100 (1/1), and the pilocytic astrocytoma was negative for BRAF (V600E) mutant protein. There were 4 neuronal or mixed glioneuronal tumors, including 3 neurocytomas and 1 malignant (high-grade) glioneuronal neoplasm, all primary ovarian and associated with teratomas (3 mature, 1 immature). These tumors expressed synaptophysin (4/4), GFAP (1/3), NeuN (1/2), and OLIG2 (1/2). Single-nucleotide polymorphism microarray analysis of the malignant glioneuronal neoplasm demonstrated a partial deletion at location (1)(p36.23p35.2) on chromosome 1p, and 2 regions of deletion at locations (19)(q11q13.12) and (19)(q13.41qter) on 19q. One neurocytoma had no 1p and 19q co-deletions. There was 1 meningioma in the pelvis. For 10 patients with embryonal tumors and follow-up, 5 were alive with no evidence of disease (mean/median: 60/52 mo), 4 were alive with recurrent disease (mean/median: 32/31 mo), and 1 died of disease (13 mo). For 5 patients with other tumor types and follow-up, all were alive without evidence of disease (mean/median: 33/30 mo). Diagnostic evaluation and classification per systems used for primary CNS tumors are recommended for the wide spectrum of CNS-type neuroepithelial tumors that can occur in the female genital tract and pelvis. Abstract : Supplemental Digital Content is available in the text.